By His Excellency Thomas Chittenden, Esquire ... A proclamation : ... to appoint Thursday the thirteenth day of November next, to be observed as a day of public thanksgiving ... Given under my hand, in the Council chamber, at Westminster, this 16th day of October, 1783 (1783)
October 16, 1783 Proclamation by Governor Thomas Chittenden setting November 13th as a day of public thanksgiving and praise to God.